Absurdity-Identity Of Body And Culture In Contemporary Art Creation - I Gede Jaya Putra; Vita Wulansari (Warna Komunikasi, 2025)
This paper discusses the creation of a contemporary artwork entitled Skibili, which emerges from the intersection between the global absurd phenomenon “Skibidi” and Balinese cultural identity. Digital anomalies such as Skibidi are understood as forms of brainrot, internet-born cultural products that are banal, repetitive, yet viral reflecting both entertainment strategies and mass consumption patterns in contemporary society. The presence of such anomalous culture collides with Balinese cultural identity rooted in sacredness and spirituality, thereby producing a new space of negotiation for the body and culture. The creative process employs the yajna approach as a symbolic, spiritual, and aesthetic method: beginning with the exploration of absurd phenomena, paying respect to traditional values, and culminating in the realization of a visual artwork using wood, charcoal, and plywood as mediums. The visualization of a human head emerging from a toilet, juxtaposed with the text “Kau yang berkata, aku yang merasa”, is read as a metaphor of a marginalized body that nevertheless retains its agency and resistance against external power. Theoretical references include Albert Camus on absurdity as a condition of meaninglessness, Michel Foucault on the body as the locus of power and discipline, and Jean Baudrillard on simulacra and hyperreality. Through this framework, Skibili is interpreted as both social critique and cultural irony: the Balinese body and identity, situated at the crossroads of sacredness and banality, threatened by absurd globalization yet simultaneously finding ways to endure through contemporary artistic expression.